2018
DOI: 10.2169/internalmedicine.9381-17
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Lung Adenocarcinoma with Nivolumab-associated Dermatomyositis

Abstract: We herein report a 42-year-old man with advanced lung adenocarcinoma and nivolumab-associated dermatomyositis. Nivolumab, an anticancer drug that is classified as an immune checkpoint inhibitor, often induces immune-related adverse events (irAEs). However, there have so far been no reports regarding nivolumab-associated dermatomyositis. This patient was diagnosed with dermatomyositis due to the presence of proximal muscle weakness with abnormal electromyography and magnetic resonance imaging findings; skin les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…Onset of symptoms tended to occur later than with other Rh‐irAEs, and prolonged immunosuppressive treatment was typically required, with few patients achieving complete symptom resolution (Table ). In general, vasculitis and CTD observed in conjunction with ICI therapy are less commonly reported, with the literature being limited to case reports and small series . As such, the optimal treatment of these patients and the impact on overall survival remain entirely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Onset of symptoms tended to occur later than with other Rh‐irAEs, and prolonged immunosuppressive treatment was typically required, with few patients achieving complete symptom resolution (Table ). In general, vasculitis and CTD observed in conjunction with ICI therapy are less commonly reported, with the literature being limited to case reports and small series . As such, the optimal treatment of these patients and the impact on overall survival remain entirely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Although various autoimmune-related adverse events related to nivolumab have been reported, nivolumab-triggered dermatomyositis, apart from myositis, is rare and there is only one case in the literature, as far as we know. Kudo et al reported the case of a patient who was treated with nivolumab for his advanced lung adenocarcinoma and was diagnosed as having nivolumab-associated dermatomyositis from his symptoms and his examinations [17]. They proposed it is necessary to consider drug-associated dermatomyositis even after nivolumab therapy [17].…”
Section: Discussionmentioning
confidence: 99%
“…Kudo et al reported the case of a patient who was treated with nivolumab for his advanced lung adenocarcinoma and was diagnosed as having nivolumab-associated dermatomyositis from his symptoms and his examinations [17]. They proposed it is necessary to consider drug-associated dermatomyositis even after nivolumab therapy [17]. In our case, however, our patient was finally diagnosed not as having nivolumab-induced myositis but as having paraneoplastic dermatomyositis because of the time course of redness of skin and the high anti-TIF1-γ antibody titer.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 There is 1 report of an inflammatory myopathy complicating nivolumab therapy that was described as dermatomyositis sine dermatitis and 1 case of dermatomyositis with classic cutaneous features induced by nivolumab. 4 , 5 However, there are no reports of Wong-type dermatomyositis during anti–PD-1 therapy. Wong-type dermatomyositis is a rare variant of dermatomyositis with fewer than 30 cases reported.…”
Section: Discussionmentioning
confidence: 99%